Ecuadorian media literacy in adolescents: Case study Loja and Zamora [Competencias mediáticas en adolescents ecuatorianos: Casos de estudio Loja y Zamora] - Rivera Rogel, D. (2016)
Currently the use of Information Technology and Communications, media skills and audiovisual literacy should relate directly to the academy, the mass media and technologies have the power not only to entertain but also to educate and contribute to the process of teaching and learning; in order to promote critical users. This research uses a survey process to identify the level of media literacy and use of ICT in the education of teenagers who live in the cities of Loja and Zamora. We conclude that there is a medium training in audiovisual and digital education by young people in the schools involved in the study. © 2016 AISTI.